Anti-Inflammatory And Analgesic Effects Of Ethanol Extract Of Dracaena Cinnabari Balf, As Endemic Plant In Yemen - AHMED ALWASHLI,; MOSA’D AL- SOBARRY,; YAHIA CHERRAH,; KATIM ALAOUI, (International Journal of Pharma and Bio Sciences, 2012)
Dracaena Cinnabari balf is species plant in agavaceae family. It is tree endemic to the Island Socotra (Yemen). The resin of this tree, dragon’s blood is known in Arabia as « dammalachawin » or Cinnabari. It has been used in traditional medicine for the treatment of gastric sores diarrhea, dysentery, as haemostatic and as anti ulcer remedy, and anti spasmodic, analgesic and anti inflammatory. In the present study, we evaluate the anti-inflammatory and analgesic activities of ethanolic extract obtained from Dracaena cinnabari balf resine, using chemical and thermal models which will induce acute pain and inflammation in animal models. The results showed the ethanolic extract has analgesic potential with 56.93% at 50mg/kg and with 67.79% at 150mg/kg as compared to aspirin 44.11% at 200 mg/kg body weight. As well as significant reduction in inflammation at the doses (50 and 150 mg/kg, p.o) (P<0.001) at 3 hours by two method. The results show that the ethanolic extract have not central analgesic effect and have peripheral analgesic as anti –inflammatory activities, supporting the traditional application of this plant in treating various diseases associated with inflammation and pain.